Character Adrift (on the Sea of Language): Robinson Crusoe, Foe, Elizabeth Costello, and the Shipwreck of Realism - James CORBY (E-REA)
This article focuses on J. M. Coetzee’s exploration of character in Foe and Elizabeth Costello, employing the metaphor of a “shipwreck” to depict the breakdown of traditional realism in literature. It examines how characters “drift” in the expanse between material reality and symbolic representation. This exploration hinges on the dual interpretations of “character”—as both a literal mark or signifier and a figurative embodiment of personhood. The discussion commences with Robinson Crusoe, positing that “drift” has been an inherent characteristic of literary characters since the inception of the novelistic tradition. The article then delves into Coetzee's nuanced narrative style, demonstrating how his characters, adrift on a sea of language and symbolism, strive to maintain their authentic existence against the encroaching tide of linguistic abstraction. This metaphorical “drift” and “shipwreck” mirror broader philosophical and cultural shifts in literature, where characters constantly oscillate between their roles as tangible entities and constructs within narrative frameworks. Coetzee’s works are shown to exemplify this tension, presenting characters who are not only vital to the storyline but also serve as metaphors for the enduring human quest for meaning and reality amid the fluidity of language and fiction.